A Case Series of Pediatric Intestinal Ganglioneuromatosis With Novel Phenotypic and Genotypic Profile - Fang, Yuan; Zhang, Ye; Dong, Rui; Wang, Yi-zhen; Chen, Lian; Chen, Gong (Frontiers in Medicine, 2022)
Introduction: Intestinal ganglioneuromatosis (IGN) is a rare condition with enteric involvement. Herein, we report a case series of pediatric IGN with novel phenotypic and genotypic profile. Methods: The clinical presentation, histopathology, immunochemistry, molecular features, treatment and prognosis of 3 cases of IGN were assessed. Results: The cases involved 3 boys with an age range of 1 year and 4 months to 8 years old, mimicking juvenile polyps or pseudomembranous enteritis. One patient carried a novel germline mutation in RTEL1 (c.296C>T/p.Pro99Leu) along with variants in F11 (c.1489C>T/p.Arg497Xaa), NBAS (c.1514delC/p.Pro505Hisfs*15), and FECH (c.315-48T>C/splicing), who died due to intractable inflammation. The other two underwent recurrence without significant signs of systemic syndrome or malignant progression. Conclusion: This case series added to the phenotypic and genotypic spectrum of pediatric IGN, which requires accumulation of more cases and research for understanding in depth.